MULTIPLYING EFFECT OF LEAN TOOLS ON THE BENEFITS OF ISO 9001 CERTIFICATION - Margaça, J.; Martins, A. (XXIV jornadas luso-espanholas de Gestão Científica, 2014)
Many Portuguese companies aim for quality certification under ISO 9001 in order to be able to compete in new of more demanding markets. Other companies do it for internal reasons. There are several benefits reported in literature that emerge from quality certification. The use of lean tools leads to improvements close to the potential certification benefits. The purpose of this research is to assess the potential multiplying effect of lean tool of the benefits of ISO 9001 certification. In order to do so a questionnaire was developed and a sample of 231 answers from certified companies was considered. Findings show that Portuguese companies experience benefits from certification that are similar to the ones reported in literature and a synergetic effect was found from the use of lean tools on the benefits from certification, in certified companies. Clues for future research are provided.